The Theory of Volkgeist in the Criminal Procedure Code - Gabriel Halsa Arifin; Mardian Putra Frans (Simbur Cahaya, 2026)
The revision of the Criminal Procedure Code (KUHAP) is an effort to build a criminal justice system that is more responsive to societal developments and the living legal values in Indonesia. The legal issue addressed in this study concerns how the theory of Volkgeist can serve as a foundation for formulating the KUHAP that reflects the character, culture, and sense of justice of the Indonesian people. This study aims to analyse the relevance of the Volkgeist theory in the formulation of criminal procedure law, particularly in regulating the concept of rechterlijk pardon (judicial pardon), restorative justice, and the fulfilment of customary obligations as a form of supplementary punishment. The research method employed is normative legal research, using a statutory and conceptual approach, through analysis of the provisions of the Criminal Procedure Code (KUHAP) and relevant legal theories. The research findings indicate that the provisions on rechterlijk pardon, restorative justice as stipulated in Article 1, point 18 of the Criminal Procedure Code, and the provisions regarding the fulfilment of customary obligations reflect the values of cooperation, deliberation, and the restoration of social relationships that have long been embedded in Indonesian society. Thus, the application of these concepts aligns with the Volkgeist theory because the law functions not only as an instrument for enforcing rules but also as a reflection of the nation’s spirit and the community’s legal culture, thereby enabling the realisation of a criminal procedural system that is more just and humane.